Métodos matemático e computacional aplicados a prospecção geoelétrica com estratificação tridimensional - Calixto, Wesley Pacheco (2012)
This work presents two optimization methods to obtain the parameters of strati- cation of the soil represented by a multilayer structure superimposed horizontally. From of the optimization methodologies applied the geoelectrical stratication is developed a method of three-dimensional stratication. The optimization methodology uses a resistivity experimental apparent curve obtained from measurements made on the soil to be stratied. The experimental curve is then compared with the resistivity theoretical apparent curve. The resistivity theoretical apparent curve is developed from the algorithm Sunde, using equations of wave propagation in strati ed ways. This algorithm takes as input the parameters of the stratied soil and as output data a resistivity theoretical apparent curve. With both experimental and theoretical curves, it is calculated the error produced in the process of horizontal soil stratication. A main feature of this model compared to the methods already developed is the optimization of the number of layers. Some errors and misconceptions committed in the horizontal soil stratication in several layers are discussed and an apparatus to assist in large scale three-dimensional soil stratication and a mathematical operator to assist in the optimization process are proposed. The results obtained with this new model are also presented and discussed.